2007
DOI: 10.1016/j.ijdevneu.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetylaspartic acid promotes oxidative stress in cerebral cortex of rats

Abstract: N-acetylaspartic acid accumulates in Canavan Disease, a severe leukodystrophy characterized by swelling and spongy degeneration of the white matter of the brain. This inherited metabolic disease, caused by deficiency of the enzyme aspartoacylase, is clinically characterized by severe mental retardation, hypotonia and macrocephaly, and also generalized tonic and clonic type seizures in about half of the patients. Considering that the mechanisms of brain damage in this disease remain not fully understood, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Cerebellum and cerebral cortex are important regions of the brain and play a prominent role in the coordination of motor movements as well as basic facets of memory and learning (Pederzolli et al, 2007). There are several investigators who have reported that these parts of the brain are highly vulnerable to oxidative stress because cerebellum and cerebral cortex have low capacity of antioxidants as compared with other tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebellum and cerebral cortex are important regions of the brain and play a prominent role in the coordination of motor movements as well as basic facets of memory and learning (Pederzolli et al, 2007). There are several investigators who have reported that these parts of the brain are highly vulnerable to oxidative stress because cerebellum and cerebral cortex have low capacity of antioxidants as compared with other tissues.…”
Section: Introductionmentioning
confidence: 99%
“…NAA inhibited the functions of catalase and GPX enzymes indicating impaired detoxification of hydrogen peroxide, but it had no effect on SOD. Acute administration of NAA also enhanced levels of hydrogen peroxide in vitro which could possibly be involved in the progression of the characteristic neurodegeneration in CD (Pederzolli et al 2007). Though these results could not be extrapolated to humans, they do reveal probable mechanisms since the oxidative stress parameters occurred with concentrations of NAA (~4fold higher) observed in the plasma and cerebrospinal fluid of patients affected by CD (Tsai and Coyle 1995).…”
Section: Oxidative Stress Theorymentioning
confidence: 86%
“…Though these results could not be extrapolated to humans, they do reveal probable mechanisms since the oxidative stress parameters occurred with concentrations of NAA (~4fold higher) observed in the plasma and cerebrospinal fluid of patients affected by CD (Tsai and Coyle 1995). Based on the supposition that NAA may promote oxidative stress in vitro and in vivo both by enhancing reactive species and diminishing antioxidant defenses, administration of antioxidants, especially vitamins E and C, could be considered as a potential adjuvant therapy for patients affected by CD (Pederzolli et al 2007).…”
Section: Oxidative Stress Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to evidence that CNS NAA accumulation may be damaging through its initiation of oxidative stress (Pederzolli et al, 2007;Surendran and Bhatnagar, 2011), antioxidants have been considered as a potential treatment for CD. Lipoic acid, being known to cross the BBB and to have a high potency, was tested in its ability to reduce signs of NAA-induced oxidative stress in 14-day-old Wistar rats (Pederzolli et al, 2010): when given before acute NAA-administration (40 mg/kg of body weight, intraperitoneally, 2-days prior to NAA), all signs of oxidative stress induced by NAA were prevented.…”
Section: Accumulation Of Naa and Oxidative Stressmentioning
confidence: 99%